Design and development of android application of static fluid e-book and calculator - Muhammad Na'im Nasiruddin, Abd Rasidi (2012)
This thesis deals with the Design and Development of Static Fluid E-Book and Calculator(Androtic). The objective of this thesis is to design and develop such Fluid Statics E-book and calculator in a convinience way which is made in android application.The thesis explains how this project is going to help students with Fluid Statics with convinience way of using it physically. It also contains the application’s content which are compatible with Diploma students who take Fluid Mechanics(Fluid Statics) subject. This application was made using an online software which built APK files using combination of user interface type coding. The application is found on Google website, named appinventor.mit.edu. As the application is build, it is also run simultaneously on an virtual android phone which linked on the online software